2005
DOI: 10.2188/jea.15.24
|View full text |Cite
|
Sign up to set email alerts
|

A Cross-Sectional Study of Primary Biliary Cirrhosis in Japan: Utilization of Clinical Data When Patients Applied to Receive Public Financial Aid

Abstract: BACKGROUND: There have not been many reports regarding primary biliary cirrhosis (PBC) in Asia. We conducted a cross-sectional study of PBC in Japan. METHODS: In fiscal year 1999, 9,761 patients with symptomatic PBC were registered to receive public financial aid from the Ministry of Health, Labour and Welfare of Japan. For our cross-sectional study we chose 5,805 patients whose clinical data had been written between 1999 and 2000, and statistically analyzed the data, including sex, age, major sympt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
21
2
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 50 publications
(31 citation statements)
references
References 16 publications
(14 reference statements)
5
21
2
1
Order By: Relevance
“…The most common EHA comorbidity was SS (19.4%), followed by autoimmune thyroid diseases (3.6%) and SLE (3.4%). These percentages were lower than in previous studies, which have reported prevalences of 13.5–36.2%, 4.4–14.4%, and 1.5–3.7% 10, 2729 , respectively. These differences might be attributable to case-finding methods and under-diagnosing as some reports from Asia found that the prevalence of EHA was much lower 16, 23 .…”
Section: Discussioncontrasting
confidence: 84%
“…The most common EHA comorbidity was SS (19.4%), followed by autoimmune thyroid diseases (3.6%) and SLE (3.4%). These percentages were lower than in previous studies, which have reported prevalences of 13.5–36.2%, 4.4–14.4%, and 1.5–3.7% 10, 2729 , respectively. These differences might be attributable to case-finding methods and under-diagnosing as some reports from Asia found that the prevalence of EHA was much lower 16, 23 .…”
Section: Discussioncontrasting
confidence: 84%
“…PBC often occurs in association with a variety of other autoimmune conditions57. Since its first description in 197079, a number of studies have found a high frequency of SSc in patients with PBC, estimating its prevalence at 2% to 18.2%57,914. These studies also indicated that PBC was most highly correlated with limited SSc and more specifically with anticentromere12,13,15.…”
mentioning
confidence: 99%
“…However, few of these patients had vasculitis. According to a cross-sectional study conducted in 5,000 patients with PBC, concurrent connective tissue diseases mainly consisted of SS (13.5%), RA (7.3%), and SSc (2.0%), although the detection rate of AMAs was high in patients with SSc and low in those with RA or SS (8). However, we cannot discount the possibility of patient differences in autoantibody reactivity to some mitochondrial proteins in those with PBC complicated by connective tissue diseases, including vasculitis, and those with PBC alone.…”
Section: Discussionmentioning
confidence: 99%